Hardware-in-the-loop simulations of an electrohydraulic power steering system for developing the motor speed map of heavy commercial vehicles. (November 2015) - Kim, Seong Han; Chu, Chong Nam
This study proposes hardware-in-the-loop simulations to develop the motor speed map of electrohydraulic power steering systems for heavy commercial vehicles. The current method that relies on the test driver's hands and feet to obtain electrohydraulic power steering motor speed maps causes a number of problems, such as inaccurate steering rates and vehicle speeds and the risk of rollover during tests. In order to overcome these weaknesses, this study employs a hardware-in-the-loop simulation system, a vehicle model, and an experimental development method. A hardware-in-the-loop simulation system was set up to simulate a steering system on the road. The system includes a system drive, data acquisition, system controller sets, and an electrohydraulic power steering system. This hardware-in-the-loop simulation system is controlled in real time because the amount of the torque from the resistant torque motor, which applies the self-aligning moments generated between the ground and the tires to the steering system, is affected by the steering angle of the steering-wheel motor. For calculation of the resistant torque with respect to various driving conditions, a vehicle model was employed in this study. It includes calculation of the self-aligning moments with the tire property data, the moments due to the kingpin inclination, the vehicle dynamics, and the steering-system modeling. The resultant values were input into the resistant torque motor. In addition to the hardware-in-the-loop simulation system and the vehicle model, the concept of a desirable steering torque which parameterizes the steering feel was introduced in this study. Using the desirable steering torque, the steering feel could be quantified, and desirable steering feels were established. In this study, in order to validate the hardware-in-the-loop simulations, a heavy commercial vehicle was designated as the target vehicle. The target vehicle's tire and specifications such as the dimensions, the weight, the steering system, and the mechanical links were adopted, and a desirable steering-torque map was established by a professional test driver. The development results were presented.